Contract Farming Led to Agrarian Torment: The Other Side of Contract Farming - Satish, B. Sowmya; Chandra, R. Satish (Indian Journal of Marketing, 2010)
As globalization and market liberalization profoundly change global agricultural production, small farms in developing countries are at a risk of being excluded from the opportunities for higher-value production arising from the opening of regional and international markets. Small farms typically lack the resources, knowledge, and information to compete in increasingly integrated markets. They are hampered by imperfect market information, poor infrastructure, and have few links with buyers in the marketing chain. These disadvantages contribute significantly to the low incomes and poverty found in developing countries like India, where small farms dominate the agricultural sector. Agriculture in India is one of the most important sectors of its economy. It is the means of livelihood of almost two thirds of the work force in the country and according to the economic data for the financial year 2006-07, agriculture accounted for 18% of India's GDP. About 43% of India's geographical area is used for agricultural activity. Though the share of Indian agriculture in the GDP has declined steadily, it is still the single largest contributor to the GDP and plays a vital role in the overall socio-economic development of India.